Vaginal washing and lubrication among female sex workers in the Mexico-US border region: implications for the development of vaginal PrEP for HIV prevention - Heather A. Pines; Shirley J. Semple; Steffanie A. Strathdee; Craig W. Hendrix; Alicia Harvey-Vera; Pamina M. Gorbach; Carlos Magis-Rodríguez; Gustavo Martinez; Thomas L. Patterson (BMC, 2018)
Abstract Background To assess the potential acceptability and inform the development of behaviorally-congruent vaginal douche- or gel-based HIV pre-exposure prophylaxis (PrEP) products, we examined vaginal washing and lubrication practices among female sex workers (FSWs) in Tijuana and Ciudad Juarez, two northern Mexico cities bordering the United States (US). Methods Two hundred and ninety-five HIV-negative FSWs (145 Tijuana; 150 Ciudad Juarez) enrolled in a behavioral HIV prevention intervention trial completed surveys assessing vaginal washing and lubrication practices, as well as motivators and barriers to performing each practice. Logistic regression was used to identify potential predictors of each practice in the past month. Results In the past month, vaginal washing was performed by 56 and 22% of FSWs in Tijuana and Ciudad Juarez (p <  0.0001), respectively, while vaginal lubrication was performed by 64 and 45% of FSWs in Tijuana and Ciudad Juarez (p = 0.001), respectively. Vaginal washing was positively associated with living in Tijuana (adjusted odds ratio [AOR] = 4.35, 95% confidence interval [CI]: 2.60-7.30), older age (AOR = 1.04 per year, 95% CI: 1.01-1.06), and vaginal lubrication (AOR = 2.99, 95% CI: 1.67-5.35), while it was negatively associated with being born in the same state as the study site (AOR = 0.50, 95% CI: 0.31-0.82), earning a monthly income ≥3500 pesos (AOR = 0.53, 95% CI: 0.28-1.00), and hazardous alcohol consumption (AOR = 0.56, 95% CI: 0.33-0.95). Vaginal lubrication was positively associated with living in Tijuana (AOR = 2.21, 95% CI: 1.37-3.54) and vaginal washing (AOR = 2.91, 95% CI: 1.64-5.18), while it was negatively associated with being born in the same state as the study site (AOR = 0.47, 95% CI: 0.29-0.75). Conclusions The moderate and high prevalence of vaginal washing and lubrication, respectively, suggest behaviorally-congruent, multi-purpose, vaginal douche- and gel-based PrEP products that simultaneously address FSWs' needs and prevent HIV infection may be acceptable to many FSWs along the Mexico-US border. Future product development and implementation should also consider the link between vaginal washing and lubrication to ensure existing practices do not undermine vaginal PrEP product effectiveness. Trial registration ClincialTrials.gov (NCT02447484).